In vitro Cytotoxicity and Genotoxicity Analysis of Ten Tannery Chemicals Using SOS/umu Tests and High-content in vitro Micronucleus Tests - Huang, Zehao; Li, Na; Rao, Kaifeng; Liu, Cuiting; Wang, Zijian; Ma, Mei (Combinatorial Chemistry & High Throughput Screening, 2018)
Background: More than 2,000 chemicals have been used in the tannery industry. Although some tannery chemicals have been reported to have harmful effects on both human health and the environment, only a few have been subjected to genotoxicity and cytotoxicity evaluations. Objective: This study focused on cytotoxicity and genotoxicity of ten tannery chemicals widely used in China. Materials and Methods: DNA-damaging effects were measured using the SOS/umu test with Salmonella typhimurium TA1535/pSK1002. Chromosome-damaging and cytotoxic effects were determined with the high-content in vitro Micronucleus test (MN test) using the human-derived cell lines MGC-803 and A549. Conclusion: The cytotoxicity of the ten tannery chemicals differed somewhat between the two cell assays, with A549 cells being more sensitive than MGC-803 cells. None of the chemicals induced DNA damage before metabolism, but one was found to have DNA-damaging effects on metabolism. Four of the chemicals, DY64, SB1, DB71 and RR120, were found to have chromosome-damaging effects. A Quantitative Structure-Activity Relationship (QSAR) analysis indicated that one structural feature favouring chemical genotoxicity, Hacceptor-path3-Hacceptor, may contribute to the chromosome-damaging effects of the four MN-test-positive chemicals.
Keywords: SOS/umu tests